Room temperature synthesis of mesoporous aggregates of anatase TiO2 nanoparticles - Deshpande, S. B.; Potdar, H. S.; Khollam, Y. B.; Patil, K. R.; Pasricha, R.; Jacob, Nalini E. (Materials Chemistry and Physics, 2006)
The controlled hydrolysis reaction of titanium tetrabutoxide in presence of acetic acid in isopropanol, i.e. in non-aqueous media was adopted in the present work for the synthesis of nanocrystalline titania followed by aging at ambient conditions for longer duration. The powder XRD shows that the as-dried precursor (without any aging) is non-crystalline in nature. However, room temperature aging for longer duration > 120 days not only helped to develop crystallinity in TiO2 nanoparticles but also led to the formation of their self-assembly towards mesoporous aggregates creating sponge like TiO2 nano-structure having high surface area similar to 250m (2) g(-1)and narrow pore size distribution of 4-5 nm. TEM observations revealed the generation of spherical TiO2 nanoparticles (4-5 nm) assembled to form stable spongy scaffold having porous network structure with pore size 5-6 nm. Also, presence of a pronounced hysteresis loop in BET isotherm is indicative of a 3D-intersection network of the pores of size 4-5 nm. Further heat-treatment to the aged precursor at 400 degrees C/2 h in air modify pore network structure due to sintering of TiO2 particles as is observed in TEM studies and lowering thereby the surface area to 125 m(2) g(-1) (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Microstructure; porous materials; sol-gel processing; titania